African Elephant Specialist Group - Dublin, Holly (Pachyderm, 2002)
This report begins by noting ongoing work of the Human Elephant Conflict Task Force, including the GIS mapping of range areas in specific study locations, the work towards translocating just over a dozen amimals from Arly to Burkina Faos which is the first elephant translocation programme in which AfESG itself is involved. The text serves as a review of the ongoing work involved in the publication of the African elephant status report (this replaces the African Elephant Database), a update on MIKE, work being undertaken by the West African and the Central African offcies, and 10 studies handled through the small grants programme which. This latter programme which provides funds of 2000-10000 USD allows for young African researchers to become directly involved in investigations which they have had some responsibility in devising.